Analysis of Sharia Digital Marketing Strategies in Increasing Sales Revenue of Tempe Chips Ipul Ngawi - Fatari, Zidan (ASEAN Journal of Halal Study, 2025)
This research aims to analyze the role of sharia digital marketing strategies in increasing the sales turnover of Ipul Ngawi tempeh chips. The implementation of digital marketing in accordance with Sharia principles, such as honesty and transparency, has become the main focus in enhancing the competitiveness of this business in an increasingly competitive market. The research method used is qualitative, with data collection techniques through in-depth interviews with business owners and secondary data analysis from the Central Bureau of Statistics (BPS) as well as other documentation. The research results show that the use of social media such as Google Maps, WhatsApp, and Instagram can expand product marketing reach, increase consumer trust, and positively impact sales revenue growth by up to 30%. However, the limited knowledge of business actors in utilizing advanced digital marketing features poses a challenge that requires further mentoring and training. Thus, the Sharia digital marketing strategy not only boosts sales but also helps strengthen the positive image of the business in the eyes of consumers. This research is expected to contribute to the development of sharia-based marketing strategies in the MSMEs sector, particularly in Ngawi Regency.